High-Strength Interstitial Alloys - Othman, Rusli (1986)
During nitriding of Mo powder. surface hardening of the sample due to the formation of b-MoN was observed. The sintered layer of S-MoN reduced the passage of nitrogen to the interior of the sample being completely nitrided and hence prevented it from only a thin layer of Mo powder was therefore completely nitrided to b-MoN in one run and so large scale production of b-MoN by this method is not possible.